2020
DOI: 10.21203/rs.2.12461/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Inappropriate child feeding practice and primary health care as major correlates of stunting and underweight among infants and young children 6-23months of age in food insecure households of Amhara and Oromia Regions, Ethiopia. A community based cross sectional study

Abstract: The authors have withdrawn this preprint due to author disagreement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Dietary diversity is vital for satisfying energy and other basic nutritional needs, especially for individuals at risk of nutrient deficiencies, such as children from low-income families. have been linked to an increased risk of poor development trajectory in children, which becomes more obvious as they grow [34][35][36].…”
Section: Discussionmentioning
confidence: 99%
“…Dietary diversity is vital for satisfying energy and other basic nutritional needs, especially for individuals at risk of nutrient deficiencies, such as children from low-income families. have been linked to an increased risk of poor development trajectory in children, which becomes more obvious as they grow [34][35][36].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, those studies also showed the chances of a child being stunted increase as they get older. This has been mainly explained by poor child feeding practice ( 37 , 38 ) and more exposure to environmental enteropathy accompanied by diarrhoea ( 22 , 39 ) . In the present study, the association might be influenced by the high performance (94⋅2 %) of vaccination ( 31 ) in the city that enables the children to cope with some enteric pathogens ( 40 , 41 ) .…”
Section: Discussionmentioning
confidence: 99%